PENGUKURAN KINERJA RANTAI PASOK PADA UMKM ROTI LEND DEUND MENGGUNAKAN METODE SUPPLY CHAIN OPERATION REFERENCE DAN ANALYTICAL HIERARCHY PROCESS - Rahman, Bayu Taufik Rahman Taufik (Prodi Teknik Industri, Fakultas Teknik, 2024)
Small and medium enterprises (SMEs) Leun Deund operating in the food industry, specifically in bread production. The enterprises is currently facing issues related to a shortage of human resources, which results in unmet consumer demand and frequent delivery delays. The purpose of this research is to improve supply chain performance based on the SCOR method indicators with the lowest values, thereby increasing production efficiency. The method employed in this study is the Supply Chain Operations Reference (SCOR) model, which measures supply chain performance through five core processes. Data analysis revealed 16 performance indicators and five key attributes, including. A questionnaire was distributed to 7 individuals in the company, and performance indicators were weighted using the Analytical Hierarchy Process (AHP) to prioritize processes for higher operational efficiency. The findings from the research suggest that the performance of the supply chain performance measurement has a final value of 28.16, which falls into the